Aa Analisys of English Textbook “Bahasa Inggris: When English Rings a Bell” - Wati, Zahwa Karunia (Institut Agama ISlam Negeri Palangka Raya, 2022)
One of the fundamental roles of textbooks is to organize content systematically so that students may acquire it quickly and correctly. By using textbooks, teachers may ensure that all of their pupils are exposed to the same material so that they can be assessed similarly. The study's methodology combined a content analysis method with a qualitative approach. Data was gathered by making an observation and keeping a record. This study's main goals are to assess textbook quality in line with the standards for good English textbooks and to make it simpler for instructors to evaluate the textbooks they are already using as consumers of textbooks. The Developing English Competencies textbook has a total score of 103, which indicates that it is very good but not highly recommended based on the seven rating criteria (below 110). The chosen textbook is appropriate for the teaching program based on the study of goals and approaches. Each section of the linguistic content is provided in a clear and easily distinguishable manner, and the content is well organized.